2021
DOI: 10.22161/ijaers.84.14
|View full text |Cite
|
Sign up to set email alerts
|

Rigor Index of juvenile cobia (Rachycentron canadum): study with anesthesia (eugenol) and hypothermia

Abstract: Consumers rigorously assess the quality of fishing products, considering mainly freshness and appearance. The slaughter method is an important factor in relation to the freshness of the fish, because it maintains important organoleptic characteristics that will influence the marketing of these products, therefore, in this study an evaluation of the Rigor Index (RI%) of cobia was performed. The following methods were used: in desensitizing with eugenol and hypothermia. Immediately after the slaughter, the monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The application of stunning methods is an essential factor in fish quality because it maintains crucial organoleptic characteristics that will influence commercialisation. Given this, Presenza et al [42] compared some preslaughter stunning methods, including eugenol stunning and hyperthermia. The authors found that slaughter preceded by the application of Eugenol resulted in full rigor mortis after 6 h, and when using the hyperthermia method, it lasted 4 h. The pre-slaughter stunning method augmented with eugenol caused less stress, positively influencing the duration of rigor mortis stages.…”
Section: Discussionmentioning
confidence: 99%
“…The application of stunning methods is an essential factor in fish quality because it maintains crucial organoleptic characteristics that will influence commercialisation. Given this, Presenza et al [42] compared some preslaughter stunning methods, including eugenol stunning and hyperthermia. The authors found that slaughter preceded by the application of Eugenol resulted in full rigor mortis after 6 h, and when using the hyperthermia method, it lasted 4 h. The pre-slaughter stunning method augmented with eugenol caused less stress, positively influencing the duration of rigor mortis stages.…”
Section: Discussionmentioning
confidence: 99%